HARMONIZATION OF INTELLECTUAL AND EMOTIONAL IN IMPROVING LESSON EFFICIENCY IN THE MODERN SCHOOL (Pedagogy of Higher and Secondary Education, 2008)
The article deals with possibilities of interaction of intellectual and motional factors of the modern lesson in providing quality education for students.